THE USAGE OF TECHNOLOGY IN FOREIGN LANGUAGE LEARNING ENVIRONMENT - Atadjanova, D.A. (SCIENCE and SOCIETY, 2024)
This article highlights the significance of using technological platforms to enhance language skills and conduct lessons successfully by creating collaborative learning environment.
Keywords: technological advancements; YouTube educational videos; Google Classroom; Zoom; developing listening and speaking